1996
DOI: 10.1088/0022-3727/29/5/032
|View full text |Cite
|
Sign up to set email alerts
|

A new method for obtaining the trap parameters of complex thermoluminescence glow peaks

Abstract: A new method is described to obtain the trap parameters of thermoluminescence (TL) glow curves including several peaks. The method starts with obtaining the trap parameters of the higher temperature glow peak. The evaluation of the trap parameters of this peak starts with determining the order of kinetics b. Two different equations are developed to estimate b. Thereafter, the activation energy E (eV) and then the frequency factor or the pre-exponential factor of this peak are determined. The shape of this pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The kinetic analysis method proposed by Rasheedy [6][7][8] was used to calculate the activation energy of the simulated glow-peaks including when the retrapping probability is greater than the recombination probability and to assess the reliability of the method by checking how well the method reproduces default values of activation energy used to generate the test glow curves. The activation energy values of the simulated glow-peaks were calculated using Eq.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The kinetic analysis method proposed by Rasheedy [6][7][8] was used to calculate the activation energy of the simulated glow-peaks including when the retrapping probability is greater than the recombination probability and to assess the reliability of the method by checking how well the method reproduces default values of activation energy used to generate the test glow curves. The activation energy values of the simulated glow-peaks were calculated using Eq.…”
Section: Resultsmentioning
confidence: 99%
“…(1) have been successfully applied to analyse glow-peaks [5]. Moreover, Rasheedy [6][7][8] has verified that the method successfully describes glow-curves that consist of one or more glow-peaks. Sunta et al [5] showed that methods based on Eq.…”
Section: Rasheedy's Activation Energy Expressionmentioning
confidence: 89%
See 3 more Smart Citations